ByzRev 07.2025.061: Anna Tiziana Drago – Owen Hodkinson (Hgg.), Ancient Love Letters. - Grünbart, Michael (The Byzantine Review, 2025)
Anna Tiziana Drago – Owen Hodkinson (Hgg.), Ancient Love Letters. Form, Themes, Approaches. Berlin – Boston: De Gruyter 2023.